Aude Thuries, L’apparition de la danse : construction et émergence du sens dans le mouvement. À partir de la philosophie de Susanne Langer - Aude Thuries (Appareil)
The aim of our work is to consider and study dance as a sense-building activity. Sense is a complex notion, which has been variously conceptualized in the course of dance history but merely investigated.In order to do so, we use the the works of Susanne Langer, a 20th century American philosopher whose writings explore the concept of “symbol”. She elaborated an original thought about dance and came up with concepts that allowed her to circumscribe the symbolic processes happening happening in the non-discursive practices, in art especially.Rather than looking at dance from an ontological point of view or as a category that gathers certain types of moves, we choose to study it as something that may appear on an intermittent basis. It allows us to give an account of the possibility of its emergence in any kind of movement, whether it happens during artistic dance, festal dance, mime, cinema, rite or within a digital creation. This decision not to reduce a priori the field of study allows us to draw a posteriori a clear distinction between dance and any other kind of moves or bodily practices. Indeed, our work tends to claim the fundamental specificity of dance, whatever environments, moments or bodies in or during which it occurs — a specificity that may be explained by its unique symbolic processes and the meanings or senses it may build or give birth to.